Durabilidade de concretos produzidos com adição de resíduos provenientes de rochas ornamentais frente à ação de íons cloreto - Dietrich, Yustane Paula (2015)
Chlorides are considered responsible for steel corrosion process initiation by the breakdown of the passive film and acceleration of electrochemical redox reactions. To prevent the chloride penetration in seaside concrete structures it is important to invest in high quality concrete. The Ornamental Rock Processing Waste (RBRO, in Portuguese) is widely produced in Espírito Santo, Brazil, and has potential to be used as mineral addition in cement based materials. This research evaluates the reinforcement steel corrosion process induced by chloride ions. Three levels of water / cement ratio was used - 0.45; 0.55 and 0.65 – and four levels of RBRO addition - 0%, 5%, 10% and 15% - by weight of the binder. Were evaluated consistency, fresh concrete specific mass; compressive strength, water absorption and capillary absorption of 216 cylindrical concrete specimens. 72 steel bars (CA -50) were embedded in 36 prismatic concrete specimens and exposed to induction and acceleration of corrosion process cycles. The specimens were stored in partial immersion in solution with 5% NaCl for 48 hours, and then they were dried in a ventilated oven thermostatically controlled at 50 °C for 5 days. The reinforcement corrosion potential was measured after immersion and after drying until the passive film breakdown. Finally, the colorimetric method was performed by spraying the AgNO3 solution (0.1 mol/L) to examine the chloride penetration in concrete specimens. Statgraphics® software was used for multiple linear regression and ANOVA analysis. Results shows that the RBRO as addition in fresh concrete can decrease its workability and density; on the other hand the axial compressive strength requirements were achieved. It was not clear the effect of RBRO in corrosion potential measurements, however, the induction time increased with increasing RBRO amounts. The 5% RBRO content proved to be the most beneficial addition ratio at durability perspective, it had the lowest contamination of chloride content by using a silver nitrate solution colorimetric method.